Strategic Management Practices on Performance of Family-Owned Firms in the Manufacturing Sector in Kenya - Rambeka, Z.; Odollo, L. (European Journal of Business and Strategic Management, 2023)
Purpose: Majority of the small and medium-size enterprises (SMEs) in Kenya are conventionally family businesses owing to their initial source of capital, ownership and day-to-day operations. Kenya's economy represents a feudal-like family economy dominated by a few well-capitalized family-owned units at both the top and mid-tier. Strategic management practices are usually geared towards increasing managerial efficiency and effectiveness so as to increase the current and future operations. The purpose of this study was to explore the effect of strategic management practices on the performance of family-owned manufacturing firms in Nairobi City County, Kenya. The specific objectives of the study included: environmental scanning, strategy formulation, strategy implementation and strategy evaluation and monitoring. Methodology: The study adopted descriptive research design using purposive sampling strategy targeting 4 heads of departments per firm from 20 firms yielding a total of 80 respondents. Structured questionnaires were used to collect primary data. Profitability ratio was collected using a secondary data collection sheet. Primary data was analyzed using SPSS version 25. Data was analyzed both descriptively as well as inferentially using and presented using statistical distribution tables. Findings: The results established that environmental scanning, strategy formulation, strategy implementation and strategy evaluation and monitoring positively and significantly affect the organizational performance of family-owned manufacturing firms. The results hence indicate that increasing each of the variable with one-unit results to increase in organizational performance of these firms with their respective beta values. Unique Contribution to Theory, Practice and Policy: The study was anchored on the following theories: agency theory, transaction cost theory, transformational and stewardship theories. The study recommends that the family-owned manufacturing firms operating in Nairobi City County, Kenya to enhance their environmental scanning, strategy formulation, strategy implementation and strategy evaluation and monitoring practices since the practices positively and significantly affects organizational performance.